ANALISIS TITIK IMPAS USAHA PENGOLAHAN BOKASHI PADA GAPOKTAN KARYA MANUNTUNG DI DESA BANYU IRANG KECAMATAN BATI-BATI KABUPATEN TANAH LAUT - Zulifah Mahdalena; Zuraida Zuraida; Jonson Mutahir (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
The study aims to determine the technical processing of Bokashi, total cost, total revenue, income and break even point. The method used in this research is survey method with observation technique participation. The sampling method by means of case studies. Results of this research note total cost at Rp. 40.2266.545, total revenue Rp. 50.000.000, income Rp. 9.773,455 and the Break even point in units of 4853,22 kg, the Break even point in selling Rp. 4.853.193,33 .